Darwin's Origin of species - Darwin, Charles, 1809-1882.; Keith, Arthur, Sir, 1866-1955. (London : J.M. Dent, 1928)
"This edition gives the copyright text embodying in full Darwin's additions and revisions ..."
"Science" - t.p.
"List of all Darwin's published volumes": p.xx.
Keywords: Evolution (Biology); Natural selection